По теореме косинусов AC^2=AB^2+BC^2-2AB*BC*cos(B) -2cos(B)=(AC^2-AB^2-BC^2)/(AB*BC) DC^2=DB^2+BC^2-2DB*BC*cos(B) = DB^2+BC^2+DB*BC*(AC^2-AB^2-BC^2)/(AB*BC)= = DB^2+BC^2+DB*(AC^2-AB^2-BC^2)/AB=12^2+18^2+12*(8^2-16^2-18^2)/16= 81 DС = 9 - это ответ см рисунок во вложении
AC^2=AB^2+BC^2-2AB*BC*cos(B)
-2cos(B)=(AC^2-AB^2-BC^2)/(AB*BC)
DC^2=DB^2+BC^2-2DB*BC*cos(B) = DB^2+BC^2+DB*BC*(AC^2-AB^2-BC^2)/(AB*BC)=
= DB^2+BC^2+DB*(AC^2-AB^2-BC^2)/AB=12^2+18^2+12*(8^2-16^2-18^2)/16= 81
DС = 9 - это ответ
см рисунок во вложении